2014
DOI: 10.1158/0008-5472.can-14-0138-t
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Tankyrases Sensitizes KRAS-Mutant Cancer Cells to MEK Inhibitors via FGFR2 Feedback Signaling

Abstract: Tankyrases (TNKS) play roles in Wnt signaling, telomere homeostasis, and mitosis, offering attractive targets for anticancer treatment. Using unbiased combination screening in a large panel of cancer cell lines, we have identified a strong synergy between TNKS and MEK inhibitors (MEKi) in KRAS-mutant cancer cells. Our study uncovers a novel function of TNKS in the relief of a feedback loop induced by MEK inhibition on FGFR2 signaling pathway. Moreover, dual inhibition of TNKS and MEK leads to more robust apopt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…However, inhibition of tankyrase alone is not sufficient to fully suppress Wnt signaling, and results in only partial or negligible tumor suppression, even in tumors with significant dependence on β-catenin (37,40). Focus has thus shifted to establishing the utility of tankyrase inhibition in combination with other therapies, and efficacy of tankyrase inhibitors in combination with PI3K/AKT inhibitors (41,42), MEK inhibitors (37) (43), EGFR inhibitors (29), and ionizing radiation(44) has been suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inhibition of tankyrase alone is not sufficient to fully suppress Wnt signaling, and results in only partial or negligible tumor suppression, even in tumors with significant dependence on β-catenin (37,40). Focus has thus shifted to establishing the utility of tankyrase inhibition in combination with other therapies, and efficacy of tankyrase inhibitors in combination with PI3K/AKT inhibitors (41,42), MEK inhibitors (37) (43), EGFR inhibitors (29), and ionizing radiation(44) has been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed significant changes to the transcriptional profile of cells treated with AZ1366 that were unrelated to canonical Wnt signaling, including dysregulation of genes involved in the cell cycle, direct changes to Axl, and EGFR expression itself, although some of these changes could be downstream of canonical Wnt target genes like MYC and CCND1. While most studies have characterized the combinatorial efficacy of tankyrase inhibitors with other therapies as being Wnt-dependent, it has been reported that synergy of tankyrase inhibition in combination with MEK inhibitors occurs independent of β-catenin, likely through a feedback loop involving FGFR2 (43). Further studies are needed to elucidate the importance of the Wnt-independent changes we observed in AZ1366 treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, several studies showed that TNKS blockade can block the proliferation of APC- mutant CRC cell lines in vitro , and some have demonstrated efficacy in vivo in GEMMs with Apc -mutant adenomas. Moreover, three recent studies showed that TNKS inhibition synergizes with approved chemotherapies [67] and drugs targeting RAS-MAPK and PI3K-AKT pathways [68, 69]. Despite the excitement of TNKS inhibition as a potential therapy to treat the majority of APC -mutant CRCs, the field is clouded by uncertainty, as multiple studies have reported conflicting data on the toxicity of TNKS blockade.…”
Section: Wnt Signaling As a Therapeutic Target In Crcmentioning
confidence: 99%
“…This suggests that 60 inhibition of parallel mitogenic signals may synergize with TNKS inhibitors to control tumor cell 61 growth. Indeed, blocking MEK, PI3K, or EGFR can enhance the anti-tumor effect of TNKS 62inhibitors 17,19,20 . Here we perform a domain-focused kinome CRISPR library screen 22 , aiming to identify 63 the most critical mitogenic signaling components that mediate resistance to TNKS inhibition, with the 93 We next introduced a domain-focused kinome library targeting 482 human kinases (~6 sgRNAs/gene) 22 94 into each LC9 line with an average representation of 2000x (Fig 1e).…”
mentioning
confidence: 99%